Expressive writing therapy for a client with low self-esteem, hallucination and post-traumatic syndrome - Septiana, Visya; Putri, Yossie Susanti Eka; Tungtrongvisolkit, Napawadee (Universitas Muhammadiyah Magelang, 2022)
Schizoaffective is a mental disorder that exhibits psychotic symptoms of schizophrenia and mood disorders which can be depressive episodes, manic episodes, or a mixture of the two episodes. This paper reported a case study of Ms R, a 24-year-old woman diagnosed with schizoaffective disorder. She has self-esteem problems, hallucinations, and post-traumatic syndrome that interfere with her productivity and social functions. The generalist psychiatric nursing care process and expressive writing therapy were implemented for her treatment for 18 days. The result supports that the combination of the two interventions positively impacted reducing signs and symptoms of low self-esteem, hallucinations, and anxiety symptoms in a client with schizoaffective. Keywords: Schizofrenia; mental health; nursing care; psychiatric nursing; community nursing